Impact of glycine and erythritol/chlorhexidine air-polishing powders on human gingival fibroblasts: An in vitro study - Weusmann, Jens; Deschner, James; Imber, Jean-Claude; Damanaki, Anna; Cerri, Paulo Sérgio [UNESP]; Leguizamón, Natalia; Beisel-Memmert, Svenja; Nogueira, Andressa Vilas Boas (Elsevier, 2022)
BACKGROUND: Supra- and subgingival air-polishing has been used in periodontitis and gingivitis therapy for years. Low-abrasive types of powders have facilitated the application in subgingival areas. In this study, the cellular effects of a glycine powder and an erythritol/chlorhexidine (CHX) powder on human gingival fibroblasts (HGF) were investigated. METHODS: HGF were obtained from sound gingiva of three healthy donors. After 12 h and 24 h of incubation time, cell viability testing and, after 24 h and 48 h, a cell proliferation assay was conducted. Additionally, the individual components erythritol and CHX were investigated for cell viability. In vitro wound healing was monitored for 48 h and scanning electron microscopy (SEM) analysis was performed after 24 h. Statistical analysis was accomplished by ANOVA and post hoc Dunnett's and Tukey's tests (p < 0.05) were performed. RESULTS: Erythritol/CHX powder and in a lower extent, glycine powder decreased cell viability and cell proliferation. The negative effect of erythritol/CHX was mainly based on the CHX component. In vitro wound healing was negatively influenced in both types of powders compared to control. Cell size was altered in both test groups, whereas cell morphology was affected only in the erythritol/CHX group. CONCLUSIONS: The investigated powders for subgingival air-polishing can influence cell viability, morphology, and proliferation, as well as wound closure in vitro. These actions on fibroblasts are discernible, with the cytotoxic effect of erythritol/CHX powder being very clear and mainly due to the CHX component. Our results suggest that subgingivally applied powders can exert direct effects on gingival fibroblasts.
Keywords: Air polishing; Cell biology; Chlorhexidine; Erythritol; Glycine; Periodontology